2022
DOI: 10.3390/su14095205
|View full text |Cite
|
Sign up to set email alerts
|

Grade Prediction Modeling in Hybrid Learning Environments for Sustainable Engineering Education

Abstract: Since mid-March 2020, due to the COVID-19 pandemic, higher education has been facing a very uncertain situation, despite the hasty implementation of information and communication technologies for distance and online learning. Hybrid learning, i.e., the mixing of distance and face-to-face learning, seems to be the rule in most universities today. In order to build a post-COVID-19 university education, i.e., one that is increasingly digital and sustainable, it is essential to learn from these years of health cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 52 publications
1
33
0
1
Order By: Relevance
“…The authors of [13] and [14] examined students' attitudes toward web-based peer review and identified key factors related to students' use and appreciation of feedback. In addition, they present an analysis of the type of feedback for the purpose of assessing the written communication skills of students using online learning tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors of [13] and [14] examined students' attitudes toward web-based peer review and identified key factors related to students' use and appreciation of feedback. In addition, they present an analysis of the type of feedback for the purpose of assessing the written communication skills of students using online learning tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Future work should focus on improving the dispersivity lab for online students, perhaps by using interactive videos as proposed by [12] and [13]. Enhancing this lab for online students is important for sustainable hybrid learning [26], i.e., the mixing of distance and face-to-face students.…”
Section: " "Watching the Dye Travel And Analysing (Sic) The Results H...mentioning
confidence: 99%
“…Nonparametric correlation tests are distribution-free hypothesis tests. They are used when samples are drawn from an unknown or nonnormal distribution [50]. Some of the most commonly used nonparametric tests include the chi-square test, Spearman's rank correlation test, and Wilcoxon's one-sample signed ranks test.…”
Section: Fig 2 Percentage Distribution Of Respondents Based On Level ...mentioning
confidence: 99%
“…In this study, Spearman's rank correlation test was used. Spearman's correlation coefficient measures the strength and direction of the association between two ranked variables when the data are measured on ordinal, interval, or ratio scales [50]. The results of the nonparametric test for this study are presented in Table 2.…”
Section: Fig 2 Percentage Distribution Of Respondents Based On Level ...mentioning
confidence: 99%